Business in practice - analysis of Evon´s performance and self-reflection from a perspective of a Director of Finance - Pietrzak, Krzysztof (2024)
Participation in Business in Practice enabled me to lead the car manufacturing company EVON for the period of 6 years as a Director of Finance. During that period I had opportunity to put the theoretical knowledge I acquired during studies into practice as well as find out about other business areas such as strategy, operations, marketing, sustainability, innovation and HR. In addition, Business in Practice enabled me to further develop my soft skills, what was possible due to participation in pitches and workshops as well as deeper understand my behavior in various business situations.